2012
DOI: 10.1111/j.1461-9563.2012.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioclimatic analyses of distributions of a parasitoid Peristenus digoneutis and its host species Lygus spp. in Europe and North America

Abstract: 1 Peristenus digoneutis Loan is a parasitoid of Lygus plant bugs, which was successfully introduced from Europe into North America in the 1980s for controlling native Lygus populations. Surveys confirmed that P. digoneutis populations have become established throughout eastern North America and that the spread of the parasitoid continues. For unknown reasons, previous releases of P. digoneutis in Western Canada were not successful. 2 A bioclimate (climex ® ; Hearne Scientific Software Pty Ltd, Australia) model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…While this may be true in terms of the fundamental niche of a species, biotic interactions such as competition, predation/parasitism and symbiosis are major determinants of the realized niche of a species and therefore of their observed distribution (Davis et al, 1998;Bullock et al, 2000;Pearson & Dawson, 2003;Ara ujo & Peterson, 2012). Indeed, the role of biotic interactions has been acknowledged by the Biotic-Abiotic-Movement (BAM) framework (Sober on & Nakamura, 2009) and in a number of recently developed species distribution models where, for example, the distribution of a parasitoid is restricted to areas where two generations of its host insect occur (Haye et al, 2013) or the BEMs of a weed and its biological control agent are overlapped to predict where the weed would be successfully controlled (Mukherjee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While this may be true in terms of the fundamental niche of a species, biotic interactions such as competition, predation/parasitism and symbiosis are major determinants of the realized niche of a species and therefore of their observed distribution (Davis et al, 1998;Bullock et al, 2000;Pearson & Dawson, 2003;Ara ujo & Peterson, 2012). Indeed, the role of biotic interactions has been acknowledged by the Biotic-Abiotic-Movement (BAM) framework (Sober on & Nakamura, 2009) and in a number of recently developed species distribution models where, for example, the distribution of a parasitoid is restricted to areas where two generations of its host insect occur (Haye et al, 2013) or the BEMs of a weed and its biological control agent are overlapped to predict where the weed would be successfully controlled (Mukherjee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, no host‐associated patterns were observed as Manitoba samples only consisted of wasps reared from L. borealis feeding on alfalfa (Table ). The Manitoba P. mellipes has only one generation per year despite the absence of P. howardi , which could be the result of their host phenology as Manitoba has a shorter summer than Alberta, thus only allowing for the development of one full generation of Lygus (Haye et al., ). While P. mellipes were only collected from Canadian prairies in this study, previous work (Zhang et al., ) and historical records have shown that there are two generations of Lygus and P. mellipes in warmer regions such as Ontario (Goulet & Mason, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Manitoba P. mellipes has only one generation per year despite the absence of P. howardi, which could be the result of their host phenology as Manitoba has a shorter summer than Alberta, thus only allowing for the development of one full generation of Lygus (Haye et al, 2013). While P. mellipes were only collected from Canadian prairies in this study, previous work (Zhang et al, 2017) and historical records have shown that there are two generations of Lygus and P. mellipes in warmer regions such as Ontario (Goulet & Mason, 2006 was not the focus of the current study, the effects of partial host and temporal separation between closely related Peristenus species and their evolutionary history could be tested using similar methods.…”
Section: Temporal Isolation But No Had Within the Peristenus Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…; Kriticos ; Haye et al. ). The CliMond 10 climate data set was used as input into the model (Kriticos et al.…”
Section: Methodsmentioning
confidence: 99%